A Survey of Graduate and Postgraduate Students' Perspective on the Use of E-learning Technology in Kerman University of Medical Sciences in 2017 - Reza Abbasi; Ahmad Raeesi; Sahar Zare (Kerman University of Medical Sciences, 2020)
Background: E-learning is one of the new methods of education that helps to increase people's knowledge and performance by using new technologies.Objectives: The purpose of this study was to investigate the attitude of graduate and postgraduate students of Kerman University of Medical Sciences toward using e-learning technology.Methods: This cross-sectional study was carried out among graduate and postgraduate students of Kerman University of Medical Sciences in autumn 2017. The data were collected by a researcher-made questionnaire whose validity and reliability was verified (α = 0.82). Data were analyzed using descriptive and analytical tests (including t-test, ANOVA, and Spearman correlation) to investigate the relationship between the mean score of e-learning usefulness and students' demographic information in SPSS software.Results: About 80% of e-learning students found it a good tool for the exchange of information and educational content between faculty and students at different universities and more than 40% believed that e-learning could improve the quality of education. About 57% of the participants were interested in using the technology. More than 70% of the students reported e-learning to be useful. Also, there was a significant relationship between the mean score of the usefulness of e-learning with age (P = 0.049), computer use skill (P = 0.025), and mobile use skill (P